Drug-Coated Balloons for the Treatment of Symptomatic Intracranial High-Grade Stenosis: A Review of the Current Rationale - Philipp Gruber; Samarth Singh; Lukas Andereggen; Lukas Andereggen; Jatta Berberat; Luca Remonda; Luca Remonda (Frontiers in Neurology, 2021)
Symptomatic intracranial atherosclerotic disease (sICAD) remains a challenging disorder in the neurovascular field. Despite best medical treatment, the recurrence rate for stroke remains high in patients with intracranial high-grade stenosis (>70–99%). Furthermore, two large randomized trials (SAMMPRIS and VISSIT) failed to prove the efficacy of percutaneous transluminal angioplasty and stenting in patients with sICAD. Drug-coated balloon percutaneous transluminal angioplasty (DCB-PTA) represents an alternative treatment modality with therapeutic benefits for interventional cardiology. However, there are very few articles in the existing literature that relate to the use of DCB-PTA in sICAD patients. Here, we aimed to review the rationale underlying the use of DCB-PTA in sICAD patients and summarize recent developments in the neurovascular field.